2011
DOI: 10.1002/vnl.20270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strengths of molten and solidified LLDPE/LDPE blends and wood/LDPE composites under tensile deformation

Abstract: The mechanical strengths of neat low‐density polyethylene (LDPE), a blend of LDPE with linear low‐density polyethylene (LLDPE), and a composite of LDPE with wood flour (wood/LDPE) were investigated in molten and solidified states under tensile deformation. The results are discussed in terms of the effects of LLDPE and wood contents, roller speed, and volumetric flow rate. In LLDPE/LDPE blends, incorporating LLDPE from 0 to 30 wt% into LDPE caused a slight increase in drawdown force, a larger fluctuation in dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 37 publications
(74 reference statements)
1
13
0
Order By: Relevance
“…For the effect of wood flour content, the drawdown force and drawability of wood/LDPE composites decreased with increasing wood flour content. From our previous study [15], the lower drawdown force of wood/LDPE composites at higher wood flour loading was probably caused by occurrences of voids and pores, and a less perfect dispersion of wood particles in the wood/LDPE composites. Adding peroxide to the wood/LDPE composite increase the drawdown force due to molecular changes as already discussed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the effect of wood flour content, the drawdown force and drawability of wood/LDPE composites decreased with increasing wood flour content. From our previous study [15], the lower drawdown force of wood/LDPE composites at higher wood flour loading was probably caused by occurrences of voids and pores, and a less perfect dispersion of wood particles in the wood/LDPE composites. Adding peroxide to the wood/LDPE composite increase the drawdown force due to molecular changes as already discussed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All tests were conducted under an extrusion melt temperature of 150°C and a distance between the die exit and the nip rollers of 90 mm. It should be noted that the melt strength measurements in this work were restricted under nonisothermal conditions [15].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, fluctuation of drawdown force was also observed during the final stage of increasing the roller speed. This was a result of draw resonance effect, which was reported and found by a number of publications 7, 10–13…”
Section: Resultsmentioning
confidence: 66%
“…The most widely used and important device for the melt strength and transient extensional viscosity measurements is so‐called “Rheotens” 7–9. Recently published works by Sombatsompop et al10–12 proposed an experimental device which was specially designed and constructed in a similar fashion to the Rheotens to determine the melt strength online in a single screw extruder using a wide range of polymer systems including homopolymers,10, 11 polymer blends and composites12 and processing and reprocessing conditions 10, 11. They suggested that the drawdown force of molten LDPE was dependent on volumetric flow rate, die temperature, roller speed, take‐up style, and the number of extrusion passes.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only few articles have been given attention to wood/polymer composite melts. Harnnarongchai et al [15] investigated the drawdown force of molten wood/LDPE composites using a filament winding technique. The results suggested that up to 10 wt% wood flour content, the drawdown force increased before it starts to decrease at a wood loading of 20 wt% and more.…”
Section: Introductionmentioning
confidence: 99%